HiNative: A Global Q&A Platform to Learn Language and Culture - Mina Jozagian; Musa Nushi; Tayyebe Izadi (Issues and Trends in Learning Technologies, 2023)
Advances in technology have had a revolutionary effect on education, making online education more accessible to everyone. These advances have also provided opportunities for development of applications or websites that could prove helpful to the process of language learning and teaching, by offering tools that could be used both inside and outside of language classroom. Among a myriad of language applications, HiNative is an app that has recently been developed. The application provides language learners with opportunity to improve their vocabulary, sentence making, and even pronunciation. one-on-one direct feedback from speakers of different languages has made HiNative a popular option for those who try to take control of their own language learning. This app could also be used to familiarize learners of a language with its culture too. This review provides a description of the attributes of this application and tries to point out the advantages and disadvantages of using this application as a supplementary language learning tool.